Selective Imaging of Late Endosomes with a pH-Sensitive Diazaoxatriangulene Fluorescent Probe. - Wallabregue, Antoine; Moreau, Dimitri; Sherin, Peter; Lorente, Pau Moneva; Jarolímová, Zdeňka; Bakker, Eric; Vauthey, Eric; Gruenberg, Jean; Lacour, Jérôme (Journal of the American Chemical Society, 2016)
Late endosomes are a major trafficking hub in the cell at the crossroads between endocytosis, autophagy, and degradation in lysosomes. Herein is disclosed the first small molecule allowing their selective imaging and monitoring in the form of a diazaoxatriangulene fluorophore, 1a (hexadecyl side chain). The compound is prepared in three steps from a simple carbenium precursor. In nanospheres, this pH-sensitive (pK = 7.3), photochemically stable dye fluoresces in the red part of visible light (601 and 578 nm, acid and basic forms, respectively) with a quantum yield between 14 and 16% and an excited-state lifetime of 7.7-7.8 ns. Importantly, the protonated form 1a·H provokes a specific staining of late endosome compartments (pH 5.0-5.5) after 5 h of incubation with HeLa cells. Not surprisingly, this late endosome marking depends on the intra-organelle pH, and changing the nature of the lipophilic chain provokes a loss of selectivity. Interestingly, fixation of the fluorophore is readily achieved with paraformaldehyde, giving the possibility to image both live and fixed cells.